Evidence that iron accelerates Alzheimer's pathology: a CSF biomarker study. Issue 5 (22nd September 2017) - Ayton, Scott; Diouf, Ibrahima; Bush, Ashley Ian
Abstract : Objective: To investigate whether cerebrospinal fluid (CSF) ferritin (reporting brain iron) is associated with longitudinal changes in CSF β-amyloid (Aβ) and tau. Methods: Mixed-effects models of CSF Aβ1-42 and tau were constructed using data from 296 participants who had baseline measurement of CSF ferritin and annual measurement of CSF tau and Aβ1-42 for up to 5 years. Results: In subjects with biomarker-confirmed Alzheimer's pathology, high CSF ferritin (>6.2 ng/mL) was associated with accelerated depreciation of CSF Aβ1-42 (reporting increased plaque formation; p=0.0001). CSF ferritin was neither associated with changes in CSF tau in the same subjects, nor longitudinal changes in CSF tau or Aβ1-42 in subjects with low baseline pathology. In simulation modelling of the natural history of Aβ deposition, which we estimated to occur over 31.4 years, we predicted that it would take 12.6 years to reach the pathology threshold value of CSF Aβ from healthy normal levels, and this interval is not affected by CSF ferritin. CSF ferritin influences the fall in CSF Aβ over the next phase, where high CSF ferritin accelerated the transition from threshold preclinical Aβ levels to the average level of Alzheimer's subjects from 18.8 to 10.8 years. Conclusions: Iron might facilitate Aβ deposition in Alzheimer's and accelerate the disease process.